U.S. LATINX ARTISTIC PRODUCTIONS: DEMOLISHING BORDERS AND DISMANTLING STEREOTYPES - Fernandes, Giséle Manganelli [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2022)
The fact that U.S. Latinx live between two worlds makes their artistic production a pungent element to obtain support for social inclusion and equality. The anxieties of these artists are related to a wide range of social and identity matters. Longing for the American Dream, these immigrants and their descendants realized the necessity to overcome not only physical but also cultural, linguistic, economic and racial barriers. In this paper, the text Entre Lucas y Juan Mejía (1992), by Julia Alvarez will base the debate related to the issue of her being hyphenated, that is, a Dominican- American, and the meaning of this situation to her identity. The play Los Vendidos (1967), by Luis Valdez, and poems by Benjamin Alire Sáenz, Jimmy Santiago Baca, Tino Villanueva as well as the movie Sleep Dealer (2009) will be analyzed in order to examine how the authors address stereotypes applied to U.S. Latinx on a daily basis.
PRODUÇÕES ARTÍSTICAS DE U.S. LATINX: DEMOLINDO FRONTEIRAS E DESMANCHANDO ESTEREÓTIPOS
Keywords: Borders; Identity(ies); Immigration; Resistance; U.S. Latinx